Batch rolling-bed dryer applicability for drying biomass prior to torrefaction - Szufa, Szymon; Ünyay, Hilal; Pakowski, Zdzislaw; Piersa, Piotr; Siczek, Krzysztof; Kabaciński, Mirosław; Sobek, Szymon; Moj, Kevin; Likozar, Blaž; Kostyniuk, Andrii; Junga, Robert (Elsevier, 2025)
This study investigates the suitability of a pilot-scale batch rolling-bed dryer for drying pine wood chips intended for torrefaction. The batch rolling bed dryer emerges as an ideal solution for further processes like torrefaction, offering a compact design and a wide range of operational parameters. Compared to rotary dryers, it occupies less volume, providing greater efficiency. Additionally, its adjustable drying airflow and compatibility with various biomass forms and particle sizes enhance its versatility. The volumetric evaporation rate was found 13.9 kg/m3 per hour for the total dryer volume and 78.8 kg/m3 for the bed volume. Mechanical tests demonstrate satisfactory operation, with potential for further optimization through impeller blade design improvements. The study also presents a simple model using the CDC modeling approach, successfully describing drying curves in most experiments, albeit with some limitations in temperature curve simulations. Overall, the rolling bed dryer proves to be a convenient solution for drying wood chips as a pretreatment for steam torrefaction, offering ease of operation and promising potential for application in continuous torrefaction lines.
Keywords: rolling bed dryer; wood chips; dryer modeling; torrefaction